Parotid abscess with facial nerve paralysis in a young healthy female - Mohamad, Irfan; Ahmad, M Zaki; Mohamad, Hazama (Bangladesh Journal of Otorhinolaryngology, 2011)
Introduction: Benign parotid lesion is rarely associated with facial nerve paralysis. If it happens, it is mainly due to the compression effect on the nerve and usually will recover after surgical intervention. Few cases of parotid abscess which involved facial nerve, mainly in elderly have been reported. Case report: In our case, we would like to report a case of parotid abscess in a young healthy female. The abscess has extended to parapharyngeal space and complicated by facial nerve paralysis. Conclusion: Conservative management was implemented while waiting for the natural recovery of facial nerve paralysis in cases of parotid abscess. These included gold-weight lid implant for corneal protection.. Despite of spontaneous recovery, there were cases the paralyzed facial nerve remained even after 6 months. Key words: Parotid abscess; facial paralysis. DOI: http://dx.doi.org/10.3329/bjo.v17i2.8858 BJO 2011; 17(2): 147-149